Combined Treatment With CCR1-Overexpressing Mesenchymal Stem Cells and CCL7 Enhances Engraftment and Promotes the Recovery of Simulated Birth Injury-Induced Stress Urinary Incontinence in Rats - Jiang, Hai-Hong; Ji, Ling-Xiao; Li, Hai-Yan; Song, Qi-Xiang; Bano, Yasmeen; Chen, Lei; Liu, Guiming; Wang, Meihao (Frontiers in Surgery, 2020)
Objective: To observe whether urethral injection of chemokine (c-c motif) ligand 7 (CCL7) and overexpressing CC receptor 1 (CCR1) in mesenchymal stem cells (MSCs) can promote their homing and engraftment to the injured tissue, and improve the recovery of simulated birth injury-induced stress urinary incontinence (SUI) in rats. Methods: Female rats underwent a dual injury consisting of vaginal distension (VD) and pudendal nerve crush (PNC) to induce SUI. Bone marrow-derived MSCs were transduced with lentivirus carrying CCR1 (MSC-CCR1) and green fluorescent protein (GFP). Forty virgin Sprague–Dawley rats were evenly distributed into four groups: sham SUI + MSC-CCR1+CCL7, SUI + MSCs, SUI + MSC-CCR1, and SUI + MSC-CCR1+CCL7 group. The engrafted MSCs in urethra were quantified. Another three groups of rats, including sham SUI + sham MSC-CCR1+CCL7 treatment, SUI + sham MSC-CCR1+CCL7 treatment, and SUI + MSC-CCR1+CCL7 treatment group, were used to evaluate the functional recovery by testing external urethral sphincter electromyography (EUS EMG), pudendal nerve motor branch potentials (PNMBP), and leak point pressure (LPP) 1 week after injury and injection. Urethra and vagina were harvested for histological examination. Results: The SUI + MSC-CCR1+CCL7 group received intravenous injection of CCR1-overexpressing MSCs and local injection of CCL7 after simulated birth injury had the most engraftment of MSCs to the injured tissues and best functional recovery from SUI compared to other groups. Histological examination showed a partial repair in the SUI + MSC-CCR1+CCL7 group. Conclusions: Our study demonstrated combined treatment with CCR1-overexpressing MSCs and CCL7 can increase engraftment of MSCs and promote the functional recovery of simulated birth trauma-induced SUI in rats, which could be a new therapeutic strategy for SUI.